Tendencje rozwojowe płac w gospodarce uspołecznionej w Polsce Ludowej - Machyńska, Irena (Wydział Prawa i Administracji UAM, 1970)
The article has been written because of the twenty-fifth anniversary of People's Poland. Its purpose is to show differences and changes in the level and dynamics of money wage in territorial cross-section by the kind of work done and by national economy divisions. The method of average salaries and wages, the one of employment structure by amount of earnings and the index method have been used to achieve the aim. Tendencies that became apparent with help of those methods may be reduced to the following general statements: — territorial differences in pay have been considerably leveled, — pay disproportions between wage-earn es and salaried workers have been notably diminished, — differences in the amount of earnings between particular divisions of national economy are still considerable, — most employees are systematically shifted from lower earnings groups to higher ones by means of an increase in average money wage of all the employees and by statutory rise in money wage.
Developmental Pay Tendencies in the Socialized Economy of People's Poland